2020
DOI: 10.21608/ejbo.2020.36166.1526
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Extract and Lithovit Mineral Fertilizer Ameliorate the Harmful Effects of Drought Stress in Wheat

Abstract: T HE effects of two levels of drought stress (25% and 50% of FC) and the control (75% FC) on the growth, some physiological processes and some metabolites in wheat (Triticum aestivum, cv. Masr 2) at seedling (30 days), vegetative (65 days) and yield (160 days) stages were studied. The ameliorative effects of the foliar spray for the harmful effects of drought by the bio-stimulant yeast extract (10%) or the mineral fertilizer lithovit (3.8%) were also studied. The results showed that both levels of drought stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Ascorbic acid (vitamin C) is one of the most common and essential vitamins due to its protective role, as it regulates various physiological processes in plants, as it performs a variety of functions such as being a major oxidation and reduction factor for enzymes involved in multiple processes including hormone biosynthesis and photosynthesis, respiration (Ortiz-Espín et al, 2017). Kasim et al (2020) observed a significant decrease in the chlorophyll content of wheat varieties when subjected to waterstress, and this decrease increased with increasing the level of water stress. The study Hussein & Khursheed (2014) about the effect of spraying ascorbic acid on the growth characteristics and some components of wheat crops exposed to drought stress conditions was determined.…”
Section: Introductionmentioning
confidence: 92%
“…Ascorbic acid (vitamin C) is one of the most common and essential vitamins due to its protective role, as it regulates various physiological processes in plants, as it performs a variety of functions such as being a major oxidation and reduction factor for enzymes involved in multiple processes including hormone biosynthesis and photosynthesis, respiration (Ortiz-Espín et al, 2017). Kasim et al (2020) observed a significant decrease in the chlorophyll content of wheat varieties when subjected to waterstress, and this decrease increased with increasing the level of water stress. The study Hussein & Khursheed (2014) about the effect of spraying ascorbic acid on the growth characteristics and some components of wheat crops exposed to drought stress conditions was determined.…”
Section: Introductionmentioning
confidence: 92%
“…Lithovit (manufactured by Zeovita-GmbH, Berlin, Germany) and quantitatively was analyzed by Wichmann and Basler (2006) as well as Wedad Kasim et al (2020). It is the first CO 2 foliar nano-fertilizer that can be applied successfully in bare fields and under glass.…”
Section: B)mentioning
confidence: 99%
“…of Economy, 2021). In Egypt, overall wheat output is insufficient to meet local demand, necessitating the immediate maximization of wheat crop production because local production is insufficient to meet annual requirements (Kasim et al, 2020). Furthermore, according to the Economic Affairs Annual Report (2017), total wheat consumption is increasing dramatically due to overall population growth of around 2.5 % per year.…”
Section: Introductionmentioning
confidence: 99%